2015
DOI: 10.1021/la505008u
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Modifying Molecular Chains in the Formation of Organized Molecular Films of Organo-Modified Nanodiamond: Construction of a Highly Ordered Low Defect Particle Layer and Evaluation of Desorption Behavior of Organic Chains

Abstract: The role of organo-modifying molecular chains in the formation of molecular films of organo-modified nanodiamond is discussed herein based on interfacial chemical particle integration of organo-modified nanodiamond having a particle size of 5 nm. The surface of nanodiamond is known to be covered with a nanolayer of adsorbed water. This water nanolayer was exploited for organo-modification of nanodiamond with long-chain fatty acids via adsorption, leading to nanodispersion of nanodiamond in general organic solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 46 publications
0
21
1
Order By: Relevance
“…It was recently shown that formation of a suitable hydrophilic covering may drastically change behavior even of individual nanodiamond grains (Fujimori et al. ). Therefore, nanodiamond grains attracted to the walls of the bubbles will experience more intense action of temperature and aggressive chemistry of the cavitating bubbles than the grains residing in the liquid bulk.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently shown that formation of a suitable hydrophilic covering may drastically change behavior even of individual nanodiamond grains (Fujimori et al. ). Therefore, nanodiamond grains attracted to the walls of the bubbles will experience more intense action of temperature and aggressive chemistry of the cavitating bubbles than the grains residing in the liquid bulk.…”
Section: Resultsmentioning
confidence: 99%
“…However, variations in hydrophilicity of the ND grains may influence the effect of the sonochemistry by several interrelated ways: heterogeneous distribution of the grains and/or their clusters between the liquid bulk and surfaces of the pre-existing and newly formed bubbles (e.g., Johnson and Cooke 1981). It was recently shown that formation of a suitable hydrophilic covering may drastically change behavior even of individual nanodiamond grains (Fujimori et al 2015). Therefore, nanodiamond grains attracted to the walls of the bubbles will experience more intense action of temperature and aggressive chemistry of the cavitating bubbles than the grains residing in the liquid bulk.…”
Section: Influence Of the Sonochemical Treatmentmentioning
confidence: 99%
“…Therefore, the adsorbed water nanolayer on the sepiolite in the reaction system was also positively charged and capable of electrostatic interactions with the phosphonate anions. Dispersions were prepared by combining an aqueous solution of sepiolite with a methanolic solution of ODP or FDP (the detailed organo‐modification procedure of sepiolite was presented elsewhere ). Toluene was then poured into the sepiolite dispersion while it was stirred, and the organo‐sepiolite particles migrated from the methanolic dispersion into the toluene phase.…”
Section: Methodsmentioning
confidence: 99%
“…For example, simple and highly efficient surface modification methods have been applied to nanodiamonds , montmorillonite clay , zirconia , zinc oxide nanodisks , magnetic fine particles , and carbon nanotubes at the oil–water interface. The resultant organo‐modified nanofillers were nanodispersed not only in a polymer matrix but also into organic solvents , indicating their amphiphilic properties .…”
Section: Introductionmentioning
confidence: 99%
“…However, regularity of layer structure in LB film is generally high, studies on polymer nanosheet and clay nanosheets dealing with this ordering are very famous. Work has also been reported on studies of novel polymer nanosheets supported by π–π interactions between carbazole groups, polymer nanosphere‐layer structures, and layered organizations of organo‐modified‐inorganic nanoparticles . In addition, changes in hydrophobic chain lengths caused by heating have also been investigated as a disordering process effect.…”
Section: Introductionmentioning
confidence: 99%